Inhibition within a premotor circuit controls the timing of vocal turn-taking in zebra finches - Jonathan I. Benichov (Nature Portfolio, 2020)
Control over when to initiate or withhold vocalizations is essential for vocal turn-taking. Here the authors investigate vocal interactions in zebra finches and show that inhibition within the premotor nucleus HVC plays an important role in the precise timing of vocal motor responses.